The Image of the Swedish-Russian War (1788–1790) on the Pages of the “Pamiętnik Historyczno-Polityczno-Ekonomiczny” (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
Taking advantage of Russia’s involvement in the conflict with the Ottoman Empire (1787–1792), in the summer of 1788 Gustav III launched a largescale naval operations and led a land offensive from Finland on the almost devoid of troops St. Petersburg. The fleet, however, failed, and the poorly-led Swedish army was stuck in southern Finland. The internal opposition and the rebellion of Finnish separatists (the Anjala Confederation), who sought to surrender this province to the Russian protectorate, were acting paralyzingly. To make matters worse, Sweden was also threatened by Denmark, which, while fulfilling its allied obligations towards Russia, started short-term military operations (August–October 1788). The Swedish-Russian war, which continued for two more years, was limited mainly to naval operations carried out with varying luck and had little impact on the course of operations on the Turkish front. The peace treaty signed in Värälä (August 14, 1790) maintained the existing borders between states (status quo ante bellum), provided for the exchange of prisoners and ensured Sweden with certain economic privileges in Russian ports. Moreover, Catherine II resigned from interfering in internal affairs of Sweden. These events were widely echoed in the Polish press, including the “Pamiętnik”, which are the subject of this article. The publisher and editor of this magazine, the Reverend Piotr Świtkowski, expressed his liking for Sweden, which was fighting against Russia, and for its king Gustav III, whom he placed in the ranks of the most eminent European rulers and indicated as a role model. He praised his Enlightened reforms, especially attempts to strengthen the royal power and struggle with the internal opposition and rebellious officers. At the same time, Świtkowski appreciated the military strength of the enemy – Russia, which Sweden had to face.